Systematic analyses for candidate genes of milk production traits in water buffalo (Bubalus Bubalis). (1st April 2019) - Du, C.; Deng, T.; Zhou, Y.; Ye, T.; Zhou, Z.; Zhang, S.; Shao, B.; Wei, P.; Sun, H.; Khan, F. A.; Yang, L.; Hua, G.
Summary: Water buffalo ( Bubalus bubalis ) is of great economic importance as a provider of milk and meat in many countries. However, the milk yield of buffalo is much lower than that of Holstein cows. Selection of candidate genes related to milk production traits can be applied to improve buffalo milk performance. A systematic review of studies of these candidate genes will be greatly beneficial for researchers to timely and efficiently understand the research development of molecular markers for buffalo milk production traits. Here, we identified and classified the candidate genes associated with buffalo milk production traits. A total of 517 candidate genes have been identified as being associated with milk performance in different buffalo breeds. Nineteen candidate genes containing 47 mutation sites have been identified using the candidate gene approach. In addition, 499 candidate genes have been identified in six genome‐wide association studies (GWASes) including two studies performed with the bovine SNP chip and four studies with the buffalo SNP chip. Genes CTNND2 ( catenin delta 2 ), APOB ( apolipoprotein B ), FHIT ( fragile histidine triad ) and ESRRG ( estrogen related receptor gamma ) were identified in at least two GWASes. These four genes, especially APOB, deserve further study to explore regulatory roles in buffalo milk production. With growth in the number of buffalo genomic studies, more candidate genes associated with buffalo milk production traits will be identified. Therefore, future studies, such as those investigating gene location and functional analyses, are necessary to facilitate the exploitation of genetic potential and the improvement of buffalo milk performance.